fMRI-Based Brain Responses to Quinine and Sucrose Gustatory Stimulation for Nutrition Research in the Minipig Model: A Proof-of-Concept Study - Coquery, Nicolas; Meurice, Paul; Janvier, Régis; Bobillier, Eric; Quellec, Stéphane; Fu, Minghai; Roura, Eugeni; Saint-Jalmes, Hervé; Val-Laillet, David (Frontiers in Behavioral Neuroscience, 2018)
The minipig model is of high interest for brain research in nutrition and associated pathologies considering the similarities to human nutritional physiology, brain structures and functions. In the context of a gustatory stimulation paradigm, fMRI can provide crucial information about the sensory, cognitive and hedonic integration of exteroceptive stimuli in healthy and pathological nutritional conditions. Our aims were (i) to validate the experimental set-up, i.e. fMRI acquisition and SPM-based statistical analysis, with a visual stimulation; (ii) to implement the fMRI procedure in order to map the brain responses to different gustatory stimulations, i.e. sucrose (5%) and quinine (10mM), and (ii) to investigate the differential effects of potentially aversive (quinine) and appetitive/pleasant (sucrose) oral stimulation on brain responses, especially in the limbic and reward circuits. Six Yucatan minipigs were imaged on an Avanto 1.5 T MRI under isoflurane anaesthesia and mechanical ventilation. BOLD signal was recorded during visual or gustatory (artificial saliva, sucrose or quinine) stimulation with a block paradigm. With the visual stimulation, brain responses were detected in the visual cortex, and thus validating our experimental and statistical set-up. Quinine and sucrose stimulation promoted different cerebral activation patterns that were concordant, to some extent, to results from human studies. The insular cortex (i.e. gustatory cortex) was activated with both sucrose and quinine, but other regions were specifically activated by one or the other stimulation. According to the hedonic value of sweet taste, sucrose stimulation induced activation in the putamen, which is involved in reward perception. Quinine stimulation induced activation in the amygdala, a brain region involved in associative conditioning such as taste aversion. Gustatory stimulation combined with fMRI analysis in large animals such as minipigs is a promising approach to investigate the integration of gustatory stimulation in healthy or pathological conditions such as obesity, eating disorders, or dysgeusia. To date, this is the first intent to describe gustatory stimulation in minipigs using fMRI.